2017
DOI: 10.1093/humrep/dex225
|View full text |Cite
|
Sign up to set email alerts
|

Which is worse? A comparison of ART outcome between women with primary or recurrent endometriomas

Abstract: Are live birth rates (LBR) different after ART cycles between women with primary or recurrent endometrioma? SUMMARY ANSWER: Women with recurrent endometrioma have similar LBR as compared to patients with primary endometrioma. WHAT IS ALREADY KNOWN: Recurrence rate can be as high as 29% after endometrioma excision. Prior studies on management of endometrioma before ART involve primary endometriomas. There is limited information regarding the prognosis of women with recurrent endometriomas. STUDY DESIGN, SIZE, D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 36 publications
1
6
4
Order By: Relevance
“…In addition, several studies have found that surgical removal of endometriotic lesions prior to ART treatment does not improve reproductive outcomes, but rather decreases the ovarian reserve [29, 30]. For example, Ata et al (2017) found that women with endometriomas had a lower ovarian reserve than age-matched controls, and this reserve was further reduced by surgical excision of endometriomas [31]. Several studies have since confirmed that the ovarian reserve damage and the IVF response after surgery was related to the size of the ovarian cysts and the presence of bilateral endometrioma [3235].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several studies have found that surgical removal of endometriotic lesions prior to ART treatment does not improve reproductive outcomes, but rather decreases the ovarian reserve [29, 30]. For example, Ata et al (2017) found that women with endometriomas had a lower ovarian reserve than age-matched controls, and this reserve was further reduced by surgical excision of endometriomas [31]. Several studies have since confirmed that the ovarian reserve damage and the IVF response after surgery was related to the size of the ovarian cysts and the presence of bilateral endometrioma [3235].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of a histologic diagnosis of endometriomas can be regarded as a limitation of the present study. As surgical excision is associated with a further decrease in ovarian reserve and does not seem to improve assisted reproduction technique outcome (Ata and Uncu, 2015;Ata et al, 2017;Hamdan et al, 2015;Somigliana et al, 2012), current indications for surgery are rather limited. These include pain unresponsive to medical treatment, organ involvement, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of the cyst was confirmed at least on two separate examinations carried out at least one month apart to rule out other haemorrhagic cysts that could be confused with an endometrioma (Exacoustos et al, 2014;Savelli, 2009). Ovarian stimulation protocols are defined elsewhere (Ata et al, 2017). Briefly, the long gonadotrophin releasing hormone (GnRH) agonist involved daily subcutaneous injections of 0.5 mg leuprolide acetate (Lucrin Daily, Abbot), starting from the mid-luteal phase of the preceding cycle until the day of ovulation trigger.…”
Section: Methodsmentioning
confidence: 99%
“…In their retrospective study, the number of dominant follicles was significantly higher in the operated ovaries with recurrence than without recurrence. 6 In line with this view, second-line surgery for recurrent endometriomas has been associated with decreased ovarian reserve [24][25][26][27][28] as well as decreased ovarian response and clinical pregnancy rates after ART cycles. 29 Our study found similar rates of ovarian response and live birth following ART cycles in women with recurrent and primary endometriomas.…”
Section: Ta B L E 2 Cycle Characteristics and Art Outcomes Of The Groupsmentioning
confidence: 91%